Aspects of psychomotor development of primary school children with hearing loss from the standpoint of Bernstein's theory of movement construction - N.I. Stepanchenko; I.B. Hrybovska; M.V. Danylevych; R.V. Hryboskyy (IP Iermakov S.S., 2020)
Purpose: As the latest research shows, psychomotor development and motor learning of deaf children is garnering a great deal of attention from scientists. Effectively correcting the psychomotor development of hearing-impaired kids requires a deep understanding of the disorders, structures, depth, and the children's potential motor learning capabilities. We believe this understanding can be reached with the Bernstein approach. However, we were able to find only a handful of studies on psychomotor development of hearing-impaired children from the point of view of the theory of how motor skills are formed. Based on this theory, the purpose of this study was to create a diagnostic program that can evaluate and analyze psychomotor disorders and uncover their mechanism in hearing impaired kids compared to their peers with normal hearing. Methods: The study included 54 children from primary schools in Lviv with normal hearing and 94 primary school children with hearing loss from the Lviv Specialized Boarding School named after Maria Pokrova №101 and the Zhovkiv Training and Rehabilitation Center "Zlagoda" (51 children with hearing loss and 43 deaf children). The research sample we chose was random and the children ranged in age from 7-8 years old. To study a single motor skill based on the involvement of multiple levels of central nervous system control, the jump model was chosen. The study consisted of 10 tests, each of which was rated on a 5point scale. Gathered and analysed data were used for the quantitative method. Result: It was established that children with hearing loss had psychomotor retardation on all motor skill levels compared to their peers with normal hearing. Hearing impaired children had a low level of static and dynamic coordination, speed of movement, and motor memory. The lowest level of development was purposeful movement. Conclusions: We identified specific psychomotor disorders in primary school children with hearing loss compared to their peers with normal hearing on all levels of motor skill formation, and found correlations between the overall assessment of hearing impaired children and the studied components by level of movement construction: for any motor activity, there is a primary level, which forms the foundation of the movement and all other levels that are activated when performing the movement. The aspects of sensory-motor functions in primary school children with hearing loss depend on the level of hearing loss and consist of an absence of coordination on multiple levels of movement construction.